Transforaminal Epidural Block and Erector Spinae Plane Block to Manage Acute Zoster-Associated Pain: A Retrospective Case–Control Study - Hyojung Soh; Yeona Ko; Jungwon Shin; Eung Don Kim (Medicina, 2024)
Background and Objectives: Achieving adequate pain reduction in the acute phase of herpes zoster is essential for preventing postherpetic neuralgia (PHN). For this purpose, appropriate antiviral medications, oral analgesic medications, and various nerve block methods could be applied. Erector spinae plane block (ESPB) is a simple, novel ultrasound-guided block technique, and its use has increased because the procedure is convenient and relatively safe. Although several cases have reported the zoster-associated pain (ZAP) control effect of ESPB, the efficacy of ESPB has not been compared with that of other types of nerve blocks for managing ZAP. This study aimed to compare the efficacy of ESPB with that of other types of nerve blocks for managing ZAP. Study Design: Retrospective case–control study. Materials and Methods: Medical records of 53 patients with acute thoracic herpes zoster were reviewed. We divided the participants into two groups: patients who received transforaminal epidural injection (TFEI) (n = 32) and those who received ESPB (n = 21). The efficacy of the procedure was assessed by a numerical rating scale (NRS) and by recording patient medication doses before the procedure and at 1 week, 1 month, 2 months, and 3 months after the procedure. Results: The time required for pain intensity to decrease to NRS ≤ 2 was not significantly different between the groups. The rate of medication discontinuation also was not different between the groups. There was no significant difference between the two groups in the proportion of clinically significant PHN (NRS ≥ 3) at any time point. Limitations: The relatively small sample size from a single center and the retrospective nature of the study served as limitations. Conclusions: The clinical effects of ESPB and TFEI were similar in patients with acute thoracic herpes zoster. ESPB could be considered an interventional option for ZAP management.